Colicin E2 Expression in Lactobacillus brevis DT24, A Vaginal Probiotic Isolate, against Uropathogenic Escherichia coli. (4th February 2014) - Trivedi, Disha; Jena, Prasant Kumar; Seshadri, Sriram
Abstract : Novel therapeutic approaches are needed to combat the urinary tract infection in women. During menstruation elevated protein concentration and increase in oxygen and carbon dioxide concentrations with decrease in vaginal Lactobacilli all together contribute to urinary tract infections. Lactobacillus species are a predominant member of the vaginal microflora and are critical in the prevention of a number of urogenital diseases. In order to increase antimicrobial potential of vaginal Lactobacilli, bacteriocin colicin E2 which has specific activity against uropathogenic Escherichia coli has been overexpressed in vaginal probiotic Lactobacillus brevis DT24. Recombinant Lactobacillus brevis DT24 expressing colicin E2 showed much higher inhibitory activity against uropathogenic Escherichia coli than wild type L. brevis DT24 in vitro . Efficacy of probiotic Lactobacillus brevis DT24 expressing colicin E2 protein is required for further in vivo evaluation.